2019
DOI: 10.1097/md.0000000000017314
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression predict unfavorable survival in acute myeloid leukemia patients

Abstract: This study aimed to investigate the prevalence/severity of anxiety and depression, and also their correlations with clinical characteristics and survival profiles in acute myeloid leukemia (AML) patients.In all, 208 AML patients and 200 age and sex-matched healthy controls (HCs) were recruited in this study. Anxiety and depression were assessed by the Hospital Anxiety and Depression Scale (HADS) in AML patients before initiating therapy and in HCs after being enrolled. Treatment response was assessed, and even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
(27 reference statements)
2
20
0
1
Order By: Relevance
“…In the United States, head and neck cancer (HNC) accounts for approximately 3.6% of cancers, with an estimated 65 000 Americans developing HNC and 14 750 dying from the disease annually 1 . In recent years, there has been mounting evidence to support the claim that depression and depressive symptoms play a role in cancer prognosis 2–9 . For instance, studies have found that depression is associated with worse all‐cause mortality for both patients with breast cancer and patients with metastatic prostate cancer 10,11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, head and neck cancer (HNC) accounts for approximately 3.6% of cancers, with an estimated 65 000 Americans developing HNC and 14 750 dying from the disease annually 1 . In recent years, there has been mounting evidence to support the claim that depression and depressive symptoms play a role in cancer prognosis 2–9 . For instance, studies have found that depression is associated with worse all‐cause mortality for both patients with breast cancer and patients with metastatic prostate cancer 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…1 In recent years, there has been mounting evidence to support the claim that depression and depressive symptoms play a role in cancer prognosis. [2][3][4][5][6][7][8][9] For instance, studies have found that depression is associated with worse all-cause mortality for both patients with breast cancer and patients with metastatic prostate cancer. 10,11 It has also been noted that patients with HNC experience rates of depression higher than those of the overall population.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the sudden onset and need to treat rapidly, patients with AML also reported feeling overwhelmed and had trouble processing the large quantity of information regarding their diagnosis and potential treatment options, which may have contributed to increases in psychological distress and feelings of helplessness [34]. In a recent publication, anxiety and depression are frequent in adult patients with AML and both predict unfavorable survival [35].…”
Section: Qol and Psychological Considerations In Amlmentioning
confidence: 99%
“…This group of patients has more than twice as high probability of death than those without cognitive deficit 37 . Similarly, fatigue, depressions, and anxiety as negative risk factors with a high incidence in this patient group are completely omitted 50,51 . Considering all the facts, it is important to find a more complex approach that includes apart from the comorbidities also cognitive function, physical function including risk of falls, nutrition, and a psychosocial state as a bare minimum.…”
Section: Geriatric Assessment and Why A Complex Approach Is Neededmentioning
confidence: 99%